Staff views around sexual expression in forensic psychiatric settings: a comparison study between United Kingdom and German-speaking countries. Issue 2 (3rd March 2020) - Di Lorito, Claudio; Tore, Madhuja; Wernli Kaufmann, Reto A.; Needham, Ian; Völlm, Birgit
ABSTRACT: Given the lack of official policies around sexual expression in several countries, members of staff are key in managing patients' sexuality in forensic psychiatric settings. This study explored staff views on sexual expression in inpatient secure services. A survey on sexual expression was administered to professionals from the United Kingdom (n = 202) and German-speaking countries (i.e. Germany, Austria and Switzerland) (n = 249). Chi-Square testing of survey items (n = 55) investigated any significant differences between samples. Most participants (54.4%) were 30–50 years old. Male to female ratio was 50:47. The UK sample had higher education than the German-speaking sample (p < 0.05). The UK sample reported more conservative views. They felt more strongly that patients should not be allowed sexual intercourse and other forms of sexual expression (e.g. touching and kissing), be provided with condoms or conjugal suites, granted privacy for masturbation and have the right to raise a child. There should be greater attention to patients' human right to sexuality in UK forensic psychiatric services. This can be pursued through raising staff awareness around patients' sexuality, implementing individualised care plans and learning from initiatives implemented in other countries. Further research is needed to identify personal and system-level mechanisms influencing staff views.